Favorable Outcomes of Preterm Infants With Parenteral Nutrition–associated Liver Disease Treated With Intravenous Fish Oil–based Lipid Emulsion. Issue 5 (May 2017) - Sorrell, Michael; Moreira, Alvaro; Green, Kay; Jacob, Rachel; Tragus, Robin; Keller, Laura; Quinn, Amy; McCurnin, Donald; Gong, Alice; El Sakka, Abeer; Mittal, Naveen; Blanco, Cynthia
ABSTRACT: Objectives: The aim of the study was to determine the acute and long-term outcomes of preterm infants treated with an intravenous fish oil–based lipid emulsion (FishLE) for parenteral nutrition–associated liver disease (PNALD). Methods: Preterm infants 14 days to 24 months of age with anatomic short gut or severe intestinal dysmotility, serum direct bilirubin ≥4 mg/dL, and requiring >60% calories from parenteral nutrition were eligible. Enrolled infants received 1 g · kg –1 · day −1 of FishLE until resolution of direct hyperbilirubinemia or return of enteral nutrition. Acute clinical effects and biochemical markers of liver function were monitored. Growth and developmental scores at 6 and 12 months postmenstrual age (PMA) were assessed and compared with controls matched by gestational age (GA). Results: Thirteen patients with mean GA of 28 ± 4 weeks were treated and compared with 119 GA-matched controls. Their mean direct bilirubin was 9.8 ± 6.4 mg/dL at enrollment. All infants had resolution of cholestasis after study completion. There were no acute adverse events, deaths, or liver/intestinal transplants. Weight and head circumference were similar between FishLE-treated patients and controls at 6- and 12-month PMA. Cognitive and motor scores were decreased at 6 and 12 months PMA in FishLE-treated infants. Logistic regression analysis showed that prolonged hospitalization was detrimental to cognitive and motor development, whereas treatment was not. Conclusions: The use of intravenous FishLEs in premature infants appears to be safe and reverses PNALD despite significant liver disease and intestinal failure. This therapy should be used in preterm infants with PNALD and followed long term to evaluate development. Abstract : Supplemental Digital Content is available in the text